MANAJEMEN HALUSINASI UNTUK MENGURANGI MASALAH GANGGUAN PERSEPSI SENSORI PADA PASIEN GANGGUAN JIWA DI RUMAH SINGGAH AL HIDAYAH MOJOKERTO : STUDI KASUS : studi kasus - Sholihah, Mar Atus; Wijaya, Arif; Pratiwi, Tiara Fatma; Fitriyah, Erna Tsalatsatul (LPPM STIKes Bahrul Ulum Jombang, 2023)
Hallucination are a condition in which a person experience changes in the number and pattern of external and internal stimuli accompanied by decreased or exaggerated response or damage responses to stimuli .(Stuart & Laraia, 2005 dalam Muhith 2018). The provision of hallucination management interventions to minimize the appearance of hallucinations can be done by teaching patients to rebuke hallucinations when they appear. This study was conducted by involving 2 respondents from Al Hidayah Mojokerto Halfway House with problems of sensory perception disorders, auditory hallucinations. Researchers conducted nursing care, namely hallucination management by applying SP 1 to SP 4 with outcome criteria guided by SLKI. Nursing care for 7 days from both clients obtained the results of verbalization hearing whispers quite decreased, sensory distortion decreased enough, hallucinatory behavior decreased enough, suspicion decreased enough, pacing decreased enough, response according to stimulus improved enough, concentration improved enough, and orientation improved enough. From the results of the study, it can be concluded that the application of hallucinatory management interventions can reduce hallucinatory signs and symptoms if done routinely and correctly, and can be one way for clients to control their hallucinations.